ANALISIS KEPUASAN KONSUMEN MELALUI KUALITAS PELAYANAN DAN KUALITAS PRODUK DI KOPI SALACA - Fadillah, Muhammad Fajar; Silaningsih, Endang; Yulianingsih, Yulianingsih (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction: This study aims to analyze consumer satisfaction at Kopi Salacca Bogor, focusing on two primary variables: service quality and product quality. Consumer satisfaction is a crucial indicator for evaluating business performance, particularly in the increasingly competitive beverage industry.Methods: A descriptive quantitative approach was employed. A total of 100 respondents were selected using accidental sampling. Data were collected using a structured questionnaire based on a five-point Likert scale, comprising 24 items measuring both the importance and performance of service and product attributes. The Customer Satisfaction Index (CSI) method was used to evaluate overall consumer satisfaction. In contrast, the Potential Gain in Customer Value (PGCV) method was applied to identify which attributes offer the most tremendous potential for improvement. Validity and reliability tests were conducted using SPSS version 25.0.Results: The CSI scores for service quality (76.4%) and product quality (76.3%) fall into the “satisfied” category. PGCV analysis revealed that service reliability, particularly in terms of consistency and punctuality, as well as product durability, including packaging and material quality, showed the highest potential for improvement. These findings suggest that although consumers are generally satisfied, strategic efforts are necessary to bridge the gap between expectations and performance. The implication is that Kopi Salacca should focus on improving product quality by utilizing better raw materials and maintaining high presentation standards, and strengthen service delivery by training its staff and enforcing operational procedures. These steps are crucial for fostering customer loyalty and enhancing long-term business competitiveness. Keywords: Customer Satisfaction, Service Quality, Café Atmosphere, Customer Satisfaction Index (CSI), Potential Gain in Customer Value (PGCV)